The amazing voyage: the third adventure in the kingdom of fantasy - STILTON, GERONIMO; GERONIMO STILTON (New York Scholastic, Inc, 2011)
Geronimo Stilton returns to the magical realm to save Queen Blossom from the Queen of the Witches.
Keywords: the magical Kingdom of Fantasy to save Queen Blossom from an endless; focus on bravery, teamwork, and finding inner strength to overcome fear